2021
DOI: 10.3390/ijms22179477
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide Nanoparticle-Induced Acute Inflammatory Response and Injury in Murine Lung Is Ameliorated by Synthetic Secoisolariciresinol Diglucoside (LGM2605)

Abstract: Metal-oxide nanoparticles (MO-NPs), such as the highly bioreactive copper-based nanoparticles (CuO-NPs), are widely used in manufacturing of hundreds of commercial products. Epidemiological studies correlated levels of nanoparticles in ambient air with a significant increase in lung disease. CuO-NPs, specifically, were among the most potent in a set of metal-oxides and carbons studied in parallel regarding DNA damage and cytotoxicity. Despite advances in nanotoxicology research and the characterization of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…lung injury [28,29]. Characterization analysis of CD in this study indicated that CD-NPs may have higher toxicity due to lower oxygen-to-carbon ratio, smaller size, and larger surface area.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…lung injury [28,29]. Characterization analysis of CD in this study indicated that CD-NPs may have higher toxicity due to lower oxygen-to-carbon ratio, smaller size, and larger surface area.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, small particles have a larger surface area. Smaller particles with larger surface area have high capacity to play a key role in nanoparticle-induced lung injury [ 28 , 29 ]. Characterization analysis of CD in this study indicated that CD-NPs may have higher toxicity due to lower oxygen-to-carbon ratio, smaller size, and larger surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Pcd1l2g is another inflammatory gene upregulated in CA77 cells after treatment ( Figure 11 ). It is clear that CuO MONPs cause increased inflammation as reported many times in the recent literature [ 41 , 42 , 43 ]. Given that CuO MONPs can bind to cell death ligands to induce non-ROS-mediated apoptosis [ 44 ], our RNAseq studies further confirm non-ROS-mediated apoptosis through increased inflammation pathways.…”
Section: Discussionmentioning
confidence: 83%
“…These in accordance with Rabia et al (2019) who suggested that CuONPs displayed histological changes which correlated with the recorded increased in liver AST and ALT. According to Pietrofesa et al (2021) inhalation of CuO NPs causes an inflammatory reaction that damages cells and lung tissues. In the current microscopic observations, the liver of CuONSp treated rats showed proliferation of bile ductules, newly developed bile ductules surrounded by mononuclear leukocytic infiltration at the end of experiment.…”
Section: Discussionmentioning
confidence: 99%